Representação da condição de saúde bucal no Facebook: análise de conteúdo, estimativa e envolvimento do usuário - André Xavier Bueno (2017)
The search for health information on internet became popular between the internet users and this occurred by the great amount of information available and the easy and free access. Social Media become the pivotal site for search for health information and the majority of American adults already did or perform the search for health information on social media. The aim of this study is to analyze the presence of oral health and odontology themes on media social Facebook and analyze the engagement of the users with these theme. Google Trends was used to define the keywords that was used for the Facebook search. A total of 19 keywords was used for facebook search and a list of 50 pages per keyword was assembled. It was realized a filtering to exclude the pages that was not associated with the theme and the pages left was classified into one of eight categories based on the page’s content. The engagement of the user was measured by the likes and content reactions. The search returned 50 pages for 13 keywords and just 2 for the keyword "clarear os dentes" and 5 for the keyword "siso dente". A total of 787 pages was found and 157 was excluded because they were not in Brazilian Portuguese and was not related with the theme. The number of pages that was analyzed is 630. The most common type of page was "Marketing" (45.7%, 288/630), followed by "Mixed" (17.1%, 108/630), "Others" (15.4%,97/630), "Information/awareness" (13%, 82/630), "Wikipedia" (4.3%, 27/630), "Blank pages" (3.3%, 21/630), "patient support" (1.1%, 7/630) and "General support" didn't have any events. The keywords "Clínica odontológica" and "Ortodontia" had 32 "Marketing" page type. Just 3 keywords ("Aparelho", "Ortodôntico" and "Aparelho Ortodôntico") had "Patient Support" page type. In the page type "Information/awareness" the keywords "Sorriso" and "Siso dente" did not have any events. The most liked pages were "Information/awareness", "Others" and "Wikipedia". The categories that had more reactions per page was "Other" and "Marketing". The reactions most common was "haha" (45.17%, 42,319/93,672) and "love" (42.22%, 38,617/93,672). The reactions with smaller quantity was "angry" (0.87%, 819/93,672) and "sad" (1.44%/ 1,353/93,672). The keywords with more likes was "Oral" (42.28%, 8,392,846/18,132,551), "Dentista" (14.95%, 2,710,960/18,132,551) and "Sorriso" (13.9%, 2,521,848/18,132,551). This research showed that the dentistry professionals that used social media focus their postings in Marketing and self-promotion. It was noted a great positive engagement of the users with the page’s content.